CircRNA_103809 Suppresses the Proliferation and Metastasis of Breast Cancer Cells by Sponging MicroRNA-532-3p (miR-532-3p) - Liu, Minfeng; Luo, Can; Dong, Jianyu; Guo, Jingyun; Luo, Qing; Ye, Changsheng; Guo, Zhaoze (Frontiers in Genetics, 2020)
Breast cancer has become one of the most serious disease threatening mankind health in the world. Accumulating studies indicated that circRNAs played an important role in the occurrence and progression of breast cancer, however, the roles of circRNA_103809 in breast cancer progression remain unclear. Therefore, in this study, we aimed to clarify the potential role and regulatory mechanism of circRNA_103809 in the development of breast cancer. Firstly, the expression level of circRNA_103809 and microRNA-532-3p (miR-532-3p) in breast cancer tissues and normal tissues were detected with the quantitative real-time polymerase chain reaction (RT-qPCR). In addition, the cell proliferation ability, metastasis ability and related pathways were identified by Cell Counting Kit-8 (CCK-8), flow cytometry, and western blot respectively. Furthermore, the connection between circRNA_103809 and miR-532-3p was detected by dual-luciferase reporter assay. Then, our data showed that circRNA_103809 was down-regulated in breast cancer tissues in contrast to adjacent nontumor tissues, and the relative expression level of circRNA_103809 was closely associated with distant metastasis size, TNM stage, HER-2 status and overall survival time. In addition, our in vitro assays showed that the overexpression of circRNA_103809 could significantly inhibit epithelial-mesenchymal transition (EMT) pathway, then suppress breast cancer cell proliferation and metastasis ability. Moreover, we also found that the antitumor effect induced by circRNA_103809 could be reversed with the addition of miR-532-3p mimics. Taken together, this study showed that circRNA_103809 could inhibit cell proliferation and metastasis in breast cancer by sponging miR-532-3p, and circRNA_103809 might be a prospective target of breast cancer therapy.